Dampak Sertifikasi Halal pada Kepuasan Konsumen (Studi Kasus di CV. Suwaga Jaya) - Amalah, Ni'matun; Nasution, Zubaidah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
Halal certification is vital in the food industry, especially in Muslim-majority areas like Gresik. This study analyzes its impact on consumer satisfaction at CV Suwaga Jaya Bu Muzanah Gresik using a qualitative case study approach. Data was collected through interviews, observations, and documentation. The findings show that halal certification significantly enhances consumer trust and satisfaction by ensuring compliance with Islamic law. It also boosts customer loyalty, as satisfied consumers tend to recommend the products. However, consumer satisfaction is also influenced by product quality, service, and market availability. Thus, while halal certification is crucial in CV Suwaga Jaya’s marketing strategy, factors like product innovation and service improvements are also necessary to maintain competitiveness.